2015
DOI: 10.1182/blood-2014-07-588590
|View full text |Cite
|
Sign up to set email alerts
|

ST3Gal-4 is the primary sialyltransferase regulating the synthesis of E-, P-, and L-selectin ligands on human myeloid leukocytes

Abstract: • A single a(2,3) sialyltransferase, ST3Gal-4, controls sLe X biosynthesis on N-and O-glycans in cells of human myeloid lineage.• Blocking this enzyme activity prevents human neutrophil adhesion to E-, P-, and L-selectin.The precise glycosyltransferase enzymes that mediate selectin-ligand biosynthesis in human leukocytes are unknown. This knowledge is important because selectin-mediated cell tethering and rolling is a critical component of both normal immune response and various vascular disorders. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 51 publications
7
90
1
Order By: Relevance
“…Data from such experiments, in tandem with genome editing methods (TALEN, CRISPR-Cas9 etc. ), may enable estimation of glycosyltransferase activities and dissection of the interdependencies among glycogenes in the same biosynthetic pathway [5,39]. …”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from such experiments, in tandem with genome editing methods (TALEN, CRISPR-Cas9 etc. ), may enable estimation of glycosyltransferase activities and dissection of the interdependencies among glycogenes in the same biosynthetic pathway [5,39]. …”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
“…In another study of O-linked glycosylation, Liu et al studied the critical enzymes (fucosyltransferases and sialyltransferases) regulating microheterogeneity in the leukocyte cell surface protein P-selectin glycoprotein ligand-1 and leukocyte cell adhesion function [45]. Predictions from such modeling have been validated by developing RNA-interference and CRISPR-Cas9 based knockouts [39,46]. In another example, Bennun et al .…”
Section: Integrating Knowledge Using Computer Models Of Glycosylationmentioning
confidence: 99%
“…1A-C could be completely blocked by anti-E-selectin mAbs (HAE-1f or P2H3) and cell binding in Fig. 1D-F was abrogated by anti-P-selectin mAb G1 (data not shown, 7, 25, 26 ).…”
Section: Resultsmentioning
confidence: 84%
“…Genome editing allows complete deletion of specific enzyme activity unlike RNAi, which is incomplete 25, 28 . HL-60 knockouts were thus generated using CRISPR-Cas9 method (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…[12] In vivo ST3Gal-IV is known to add sialic acids onto the terminal galactose of N- and O-glycans, [13] however, the in vitro specificity and substrate scope of recombinant human ST3Gal-IV for cell-surface glycan editing has not been characterized. Kinetic analysis using type II LacNAc as the acceptor substrate revealed that this enzyme has excellent activity toward the natural donor substrate CMP-Neu5Ac (CMP-Sia) with K m of 0.0734 mM and V max of 0.0478 nmol min −1 .…”
mentioning
confidence: 99%